Peran Positif Penyesuaian Diri Terhadap Efikasi Diri Pada Mahasiswa Baru - Utia Ningsih, Ike (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
This study aims to determine whether there is a relationship between self-efficacy and self-adjustment to college in new students of the Faculty of Psychology UIN Raden Fatah Palembang. This study was conducted on new students of the Faculty of Psychology, Universitas Airlangga class of 2013 with a total of 89 research subjects. The data collection tool used is a questionnaire in the form of a General Self-Efficacy scale consisting of 10 items and a self-adjustment scale to college consisting of 24 items. Based on the output, it is known that the significance value or Sig. (2-tailed) of 0.002, because the value of Sig. (2-tailed) 0.002 < smaller than 0.05 or 0.01, it means that there is a significant relationship (means) between the self-adjustment variable and self-efficacy in new students. The results of the research data analysis obtained a correlation coefficient of 0.467 with a significance level of 0.000. So it can be concluded that there is a significant relationship between self-efficacy and self-adjustment to college in new students of the Faculty of Psychology UIN Raden Fatah Palembang with the strength of the relationship in the moderate category.